Implementation of an optimised tele-medicine platform for stroke in South Australia improves patient care - Kurunawai, Craig; Chen, Chushuang; Willcour, Matthew; Tan, Aaron; Mahadevan, Joshua; Waters, Michael; Harvey, Jackson; Van Eunen, Joanne; Dixon, Karen; Piantedosi, Bianca; Bivard, Andrew; Parsons, Mark William; et al. (Frontiers in Neurology, 2024)
Background Patients with a large vessel occlusion require a transfer from a primary stroke centre to access thrombectomy, often over significant distances in regional areas. We sought to optimise stroke care access in the regional South Australian Tele-Strokeservice (SATS) to improve patient access to thrombectomy. Methods We undertook a 24-month interventional historically controlled cohort study comparing acute stroke care metrics in the SATS. This consisted of a 12-month control period and a 12-month intervention monitoring period. The study intervention considered of an education package provided to the regional hospitals, a stroke neurologist roster to receive consultations and the intervention of a centralised tele-stroke system to provide treatment advice and organise patient transfers where needed. The SATS services 61 rural hospitals in South Australia, and Alice Springs in the Northern Territory. Suspected acute stroke patients presenting to the participating regional hospitals in SATS network where a telehealth consultation took place. Results Over the study period, there were 919 patient referrals, with 449 consultations in the pre-intervention phase and 470 in the post-intervention phase. Demographic features in both epochs were similar. The post-intervention phase was associated with shorter door-to-scan time (35 min, IQR: 18,70; vs. 49 min, IQR:25,102, p < 0.0001), faster door-to-thrombolysis time (58 min, IQR: 39,91, vs.83 min, IQR: 55,100, p = 0.0324) and a higher portion of patients treated with thrombectomy (54, 11.5% vs. 26, 5.8%, p = 0.002). Conclusion An optimised implementation of a streamlined telehealth platform with ongoing education and feedback to referring sites was associated with improved stroke workflow metrics and higher thrombectomy rates.